Review of Philip Carabott’s, Yannis Hamilakis and Eleni Papargyriou (eds), Camera Graeca: Photographs, Narratives, Materialities - Petsini, Penelope (Historein, 2016)
Philip Carabott, Yannis Hamilakis and Eleni Papargyriou, eds. Camera Graeca: Photographs, Narratives, Materialities. Farnham: Ashgate, 2015. 375 pp.